Clusterin secretion is attenuated by the proinflammatory cytokines interleukin‐1β and tumor necrosis factor‐α in models of cartilage degradation. Issue 5 (17th August 2020) - Matta, Csaba; Fellows, Christopher R.; Quasnichka, Helen; Williams, Adam; Jeremiasse, Bernadette; Allaway, David; Mobasheri, Ali
Abstract: The protein clusterin has been implicated in the molecular alterations that occur in articular cartilage during osteoarthritis (OA). Clusterin exists in two isoforms with opposing functions, and their roles in cartilage have not been explored. The secreted form of clusterin (sCLU) is a cytoprotective extracellular chaperone that prevents protein aggregation, enhances cell proliferation and promotes viability, whereas nuclear clusterin acts as a pro‐death signal. Therefore, these two clusterin isoforms may be putative molecular markers of repair and catabolic responses in cartilage and the ratio between them may be important. In this study, we focused on sCLU and used established, pathophysiologically relevant, in vitro models to understand its role in cytokine‐stimulated cartilage degradation. The secretome of equine cartilage explants, osteochondral biopsies and isolated unpassaged chondrocytes was analyzed by western blotting for released sCLU, cartilage oligomeric protein (COMP) and matrix metalloproteinases (MMP) 3 and 13, following treatment with the proinflammatory cytokines interleukin‐1β (IL‐1β) and tumor necrosis factor‐α. Release of sulfated glycosaminoglycans (sGAG) was determined using the dimethylmethylene blue assay. Clusterin messenger RNA (mRNA) expression was quantified by quantitative real‐time polymerase chain reaction. MMP‐3, MMP‐13, COMP, and sGAG release from explants and osteochondral biopsies was elevated with cytokine treatment, confirming cartilage degradation in these models. sCLU release was attenuated with cytokine treatment in all models, potentially limiting its cytoprotective function. Clusterin mRNA expression was down‐regulated 7‐days post cytokine stimulation. These observations implicate sCLU in catabolic responses of chondrocytes, but further studies are required to evaluate its role in OA and its potential as an investigative biomarker.